2019
DOI: 10.1111/jora.12518
|View full text |Cite
|
Sign up to set email alerts
|

Social Inclusion of Refugee and Native Peers Among Adolescents: It is the Language that Matters!

Abstract: This study investigated the role of refugee status and language skills for adolescents’ inclusion or exclusion decisions in hypothetical intergroup scenarios. 100 German adolescents (Mage = 13.65 years, SD = 1.93) were presented three scenarios in which groups of adolescents are planning leisure time activities, and peers from their own country (Germany) versus another country (Syrian refugees) with either good or bad German skills want to join them. Whereas adolescents’ inclusion decisions did not differ betw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 68 publications
2
33
0
1
Order By: Relevance
“…One of the more salient features of foreign status is linguistic proficiency in the official language of the receiving society. Migrant children and adolescents lacking proficiency in the language of the receiving society are more prone to experiencing discrimination as well as social exclusion, particularly in school contexts (Beißert, Gönültaş, & Mulvey, 2020; Buchanan et al., 2018; Kiramba et al., 2020). The negative implications of foreign status manifest in distinct ways in cases where migrants share the same language as native‐born individuals in the receiving society.…”
Section: An Interdisciplinary Framework Of Adaptationmentioning
confidence: 99%
“…One of the more salient features of foreign status is linguistic proficiency in the official language of the receiving society. Migrant children and adolescents lacking proficiency in the language of the receiving society are more prone to experiencing discrimination as well as social exclusion, particularly in school contexts (Beißert, Gönültaş, & Mulvey, 2020; Buchanan et al., 2018; Kiramba et al., 2020). The negative implications of foreign status manifest in distinct ways in cases where migrants share the same language as native‐born individuals in the receiving society.…”
Section: An Interdisciplinary Framework Of Adaptationmentioning
confidence: 99%
“…A study from Germany showed the importance of language for the social inclusion of adolescent refugees with their native peers. 25 A change made at this TAC is that all of the teachers in the camps are native speakers of Turkish and not Syrian teachers or volunteers. This in turn has increased Turkish literacy rates for refugee children.…”
Section: Discussionmentioning
confidence: 99%
“…Over a third of the studies published, this last decade relies on multiple informants (self-reports, parent, peer, teacher, or school reports), and includes in the design an assessment of multiculturalism ideology at national and school levels (e.g., Brown & Chu, 2012;Sam, 2018), and nonimmigrants' attitudes toward outgroups or immigrants and refugees in particular (e.g., Beißert, G€ on€ ultas ß, & Mulvey, 2020;Gr€ utter & Tropp, 2018). Data are often analyzed through the use of multilevel models to account for the nestedness of individuals in schools, communities, or countries, and to examine the effect of higher-level contextual variables on immigrant youth adaptation (e.g., Leventhal & Shuey, 2014;Zimmerman & Farrell, 2017).…”
Section: Methodological and Statistical Approaches For Addressing Dst Principlesmentioning
confidence: 99%